THE QUALITY OF COCONUT OIL PREPARED USING HEATING TECHNIQUE WITH ADDITION OF CARROT POWDER (Daucus carrota L) AS NATURAL ANTIOXIDANT - Suaniti, N. M.; Manurung, M.; Ratnayani, O.; Dewi, A. A. I. S. J. (Jurnal Kimia (Journal of Chemistry); Vol.13 No.1 Januari 2019DO - 10.24843/JCHEM.2019.v13.i01.p17, 2019)
Spoilage of coconut oil is indicated by rancidity caused by the oxidation and hydrolysis reactions. One of the efforts that can be carried out to inhibit the rancidity is by adding a natural antioxidant, such as carrot ( Daucus carrota L) powder, into the coconut oil. This research aimed to find out the effect of the addition of carrot powder into the coconut oil on some parameters namely iodine number, peroxide number, FFA level, acid value and water content. The coconut oil was prepared by heating technique followed by the addition of carrot powder in the ratio of coconut oil:carrot of 100:1, 100:2, 100:3, 100:4, 100:5, and coconut oil:BHT (Butyl Hydroxy Toluene) of 100:1 as the positive control. The results were then compared to the Indonesian National Standard of SNI 01-2902-1992. It was found that the coconut oil added with carrot powder in the ratio of 100:4 showed the best quality with iodine number of 8.4092 ± 0.5761g iodine/100g, peroxide number of 3.2363 ± 1.9168mg O 2 /100g, Free Fatty Acid level (FFA) of 0.1676 ± 0.0037 %, acid value of 0.4656 ± 0.0119mg KOH/g and water content of 0.1038 ± 0.0068 %. The characterization using FTIR (Fourier-transform infrared spectroscopy) of such quality of coconut oil indicated some functional groups of OH, CH, CH 3, C=O, CºC aliphatic and C=C aliphatic were contained.